Desenvolvimento de bioprocesso para imobilização de microorganismos rizosféricos de Ocotea odorífera (Vell.) Rohwer, Lauraceae, visando a produção de mudas - Bett, Larissa Amanda (2017)
Ocotea odorifera (Vell.) Rohwer is a forest specie characteristics of Araucaria Forest, physiognomy of the Atlantic Forest prevailing in Southern Brazil. It is an endangered species due the intense habitat fragmantation, human disturbance and exploitation of ther natural populations for economic purposes, which is compunded by difficult natural and artificial regeneration. Forest Biotechnology acts as a tool for the implementation of ex situ conservation actions, providing means to enable the perpetuation of forest species threatened with extinction. In this context, this study aimed to develop an efficient bioprocess for the propagation of Ocotea odorifera, using rhizospheric microorganisms. For this, the community of microorganisms in association with the rhizosphere of seedlings collected in a natural environment was carried out in a Natural Heritage Private Reserve (NHPR) located in the city of Lapa, PR. After extraction of the soil, the material was submitted to serial dilutions, making it possible to obtain Colony Forming Units (CFUs), which were subsequently selected and molecularly identified by Polymerase Chain Reaction and sequencing of the 16S and IT5 genes. Seven microorganisms were selected. Biomass was obtained from each microorganism by fermentation in a bioreactor. The microorganisms presented different fermentation times, between 22 and 36 hours, for the morphotypes four and seven, respectively. After fermentation, the microorganisms were immobilized on alginate and chitosan microspheres. The microspheres produced maintained uniform sizes and showed resistance to spherical shape maintenance. Immobilization by means of the alginate and chitosan microspheres with subsequent lyophilization allows the controlled release of the microorganisms in the medium, giving a greater probability of success to the propagation process, besides being more economically viable due to the ease of storage and transportation. The microspheres, thus represent a viable alternative for the immobilization of selected rhizosphere microorganisms from Ocotea odorifera.